EDUCATION STATUS OF MUSLIM WOMEN IN KAYALPATTINAM - S. Benazeer (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
In Tamil Nadu, education was regarded as an important aspect of society. During the pre-British period, Muslim women received little attention in education, as male education dominated. Though Islam encouraged women’s learning, social customs like the purdah system and early marriages restricted their access. The arrival of the British and the influence of Christian missionaries marked a turning point in Muslim women’s education. Before 1850 A.D., there were no organized Muslim institutions in Tuticorin; education took place at teachers’ homes where Lebbais taught the Quran, Arabic, moral values, Tamil, and basic mathematics. Most families depended on fishing, weaving, cultivation, and cattle grazing for livelihood, which limited girls’ education. Kayalpattinam, an ancient settlement famous since the Sangam age, along with Korkai, Tiruchendur, and Tuticorin, became centers symbolizing Muslim culture and learning in southern Tamil Nadu.